Fenomena Internet Addiction Disorder Pada Gen Z - Ogianto Putra; Dinda Rakhma Fitriani (Kanal: Jurnal Ilmu Komunikasi, 2019)
This research aims to determine and analyze thePhenomenon Internet Addiction Disorder of Gen Z.The method used is a descriptive qualitative approach, in which the researcher makes observations involved, structured interviews that have been made previously with reference to aspects or indicators of existing variables.The theory used is the CMC (Computer Mediated Communication) theory and the Lifestyle theory.The results show that the role of social media Instagram has a huge impact on progresslifestyle of the younger generation.Instagram it's not just to post pictures and videos, but makes it easy for users to find information or anything they want. Even thoughInstagram has many positive impacts, for them it is possible to have many negative impacts. The negative impact of excessive use of social media can reduce the social, health and mental illness of the younger generation.